Pengembangan E-LKPD Berbasis Problem Solving Materi Siklus Air Kelas V Di SDN Umbul Tengah 1 - Alifa Muslimah; Encep Andriana; Lukman Nulhakim (STKIP Melawi, 2022)
Abstract: This study aims to develop problem solving-based E-LKPD andtest the effectiveness of the product through the expert test stage and to findout how students respond to the problem solving-based E-LKPD developed.LKPD is a learning device which contains activities that involve studentsindependently and actively and has been designed according to the conditionsand situations in the surrounding environment in a programmatic manner. Thisstudy uses the Research Development (RD) research method using theADDIE model, with several stages, namely Analysis, Design, Development,Implementation, and Evaluation. This research was conducted at SDN UmbulTengah 1 with the research subject of class V students as many as 18 studentswith details of students in small group trials. The instrument used is aquestionnaire sheet for validation of material experts, media experts, andlinguists, as well as student responses. The results of the research obtained arethe feasibility of problem solving-based E-LKPD based on the assessment ofmaterial experts who get very decent criteria with a percentage of 88%, mediaexperts get very decent criteria with a percentage of 87%, and linguists getvery decent criteria with a percentage of 86%. Students gave a positiveresponse with a percentage of 99.2% and were included in the very goodcategory. The development of problem solving-based E-LKPD is veryfeasible to use and get a positive response to be used as teaching materials. Keywords: Problem Solving-Based E-LKPD, Science Learning, Grade V Elementary School Abstrak: Penelitian ini bertujuan untuk mengembangkan E-LKPD berbasisproblem solving dan menguji keefektifan produk melalui tahap uji ahli sertauntuk mengetahui bagaimana respon peserta didik terhadap E-LKPD berbasisproblem solving yang dikembangkan. LKPD adalah sebuah perangkatpembelajaran yang di dalamnya berisikan kegiatan yang melibatkan pesertadidik secara mandiri dan aktif serta telah di rancang sesuai dengan kondisi dansituasi di lingkungan sekitar secara terprogram. Penelitian ini menggunakanmetode penelitian Research Development (RD) dengan menggunakanmodel ADDIE, dengan beberapa tahapan yaitu Analysis, Design,Development, Implementation, Evaluation. Penelitian ini dilakukan di SDNUmbul Tengah 1 dengan subjek penelitian peserta didik kelas V sebanyak 18siswa dengan perincian peserta didik pada uji coba kelompok kecil.Instrument yang digunakan berupa lembar angket untuk validasi ahli materi,ahli media, dan ahli bahasa, serta respon peserta didik. Hasil penelitian yangdidapatkan adalah kelayakan E-LKPD berbasis problem solving berdasarkanpenilaian ahli materi mendapat kriteria sangat layak dengan persentase sebesar88%, ahli media mendapat kriteria sangat layak dengan persentase sebesar87%, dan ahli bahasa mendapat kriteria sangat layak dengan persentasesebesar 86%. Peserta didik memberikan respon positif dengan persentasesebesar 99,2% dan masuk dalam kategori sangat baik. Pengembangan ELKPDberbasis problem solving sangat layak digunakan dan mendapatkan respon positif untuk dijadikan sebagai bahan ajar. Kata Kunci: E-LKPD berbasis Problem Solving, Pembelajaran IPA, Kelas VSD